Physiological Responses of Rice to C02 Enrichment and Rising Temperature - Xie, Liyong; Ju, Hui; Lin, Erada; Ma, Zhanyun (Annals of Arid Zone, 2016)
The increase of atmospheric C02 concentration, observed in recent years, will continue and may reach 550 ppm by 2050s. The increase of atmospheric C02 has the potential to enhance the crop yields, as it is one of the main sources for plant photosynthesis. However, rising temperatures are likely to adversely affect physiology and development of crop. The integrated impacts on crops, caused by increases in atmospheric C02 concentration and temperatures over the long term have not been clearly understood so far. CAAS designed the gradient experiment to reveal the effect of rising atmospheric C02 and temperatures on growth, development and yield of rice (Oryza sativa L.)in Northern China. In this experiment, physiological characteristics of rice were measured during the season (after transplanting) in a half-open C02-temperature Gradient Chamber (CTGC). The CTGC was used to treat the rice crop with different C02 concentrations and temperatures in the field. The results showed that, the grain filling dry matter accumulation and yields increased signficantly at 550 ppm C02 +1.0°C and 650 ppm C02 +lSC compared to the CK. The harvest index (HI) at elevated C02 was lower than that of CK. The treatments 550 ppm C02 +1.0°C and 650 ppm C02 +1.5°C increased the chlorophyll content of the rice leaves to 13.41%-16.74% above the CK (outside ambient plots), and increased further in later growth stages. The chlorophyll a/b ratio remained unaffected. The soluble sugar and soluble protein contents increased in Iants grown at 550 ppm C02 +1.0°C and 650 ppm C02 +l.5°C compared to CK. The results indicate that C02 fertilization effect also had potential to increase rice grain yield. Key words: C02 enrichment, temperature rise, rice (Oriza sativa L.), growth and yield, physiological indices.